Accumulation of Microplastics in African Sharptooth Catfish Clarias gariepinus from Ikpoba Reservoir, Benin City, Nigeria - Oiseoje Michael, Wangboje; Eghe, Oshodin, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
Microplastics (MPs) are minute pieces of plastic of synthetic origin. The potential threat posed by MPs to human health warranted this research on the Ikpoba Reservoir in Benin City, Nigeria which was achieved by Fourier Transform Infrared Spectroscopy (FTIR) following the extraction of organic matter from the intestinal tract of Clarias gariepinus fish. The mean levels of accumulated MPs in C. gariepinus (mean total length 29.95 ± 2.76 cm, mean weight 798 ± 2.15 ranged from 0.91 (June) at the Okhoro station to 1.45 (August) also at the Okhoro station with no observed significant difference (p>0.05) in the levels of MPs in C. gariepinus between stations while the mean plastic load ranged from 0.31 (June) at the Okhoro station to 0.97 (July) at the Low lift pump station with an observed significant difference (p<0.05) in the plastic load in C. gariepinus between months (June, July and August) at the Midpoint and Okhoro stations. Polyethylene pellets dominated the microplastic particles having the highest quota of 33.33%. The estimated daily intake values (Mg/person/day) for MPs ranged from 0.00054 (Okhoro station) to 0.00059 (Midpoint station) with an overall value of 0.00059. A triad approach to contain the menace of MPs was suggested to include routine monitoring, enforcement of stringent laws on the disposal of plastics and public enlightenment in order to safeguard the integrity of this ecosystem and to protect public health.